Chondrocyte cell adhesion on chitosan supports using single-cell atomic force microscopy. Issue 1 (2nd January 2022) - García García, Christian Enrique; Verdier, Claude; Lardy, Bernard; Bossard, Frédéric; Soltero Martínez, J. Félix Armando; Rinaudo, Marguerite
Abstract: In this work, functional scaffolds based on electrospun chitosan nanofibers are unprecedentedly studied in terms of their force cell adhesion response. To prove cell compatibility of this biomaterial, chondrocyte interactions are investigated using atomic force microscopy in which a single cell is fixed to the cantilever and approached to the chitosan mat for a given contact time. Then, the cantilever is retracted and cell interactions are studied. Force jumps distribution for cell detachment is described and the adhesion energy is determined comparing nanofiber mats with homogeneous films and a BSA coated surface as control. Force adhesion on chitosan films, equals 460 ± 150 pN, is found slightly higher than on porous fiber mats (410 ± 135 pN) indicating that more cell-substrate bonds could be formed on a flat contact surface for a contact time of 60 s. The same trend was observed for a contact of 120 s between the cell and the substrate. The adhesion on hydrophilic chitosan surface at t = 60 s, is much larger than on the control surface (210 ± 90 pN) due to its positive character and ability for H-bond stabilization.